Plasma-Exposure-Induced Mobility Enhancement of LiTFSI-Doped Spiro-OMeTAD Hole Transport Layer in Perovskite Solar Cells and Its Impact on Device Performance - Qu, Hao (Materials (Basel), 2019)
2,2′,7,7′-Tetrakis(N,N-di-p-methoxyphenyl-amine)-9,9′-spirobifluorene (spiro-OMeTAD) film currently prevails as hole transport layer (HTL) employed in perovskite solar cells (PSCs). However, the standard preparation method for spin-coated, Lithium bis(trifluoromethylsulfony) imide (LiTFSI)-doped, spiro-OMeTAD HTL depends on a time-consuming and uncontrolled oxidation process to gain desirable electrical conductivity to favor device operation. Our previous work demonstrated that ~10 s oxygen or oxygen containing gas discharge plasma exposure can oxidize spiro-OMeTAD HTL effectively and make PSCs work well. In this communication, hole-only devices are fabricated and in-situ current density-voltage measurements are performed to investigate the change in hole mobility of LiTFSI-doped spiro-OMeTAD films under plasma exposure. The results reveal that hole mobility values can be increased averagely from ~5.0 × 10(−5) cm(2)V(−1)s(−1) to 7.89 × 10(−4) cm(2)V(−1)s(−1) with 7 s O(2) plasma exposure, and 9.33 × 10(−4) cm(2)V(−1)s(−1) with 9 s O(2)/Ar plasma exposure. The effects on the photovoltaic performance of complete PSC devices are examined, and optical emission spectroscopy (OES) is used for a diagnostic to explain the different exposure effects of O(2) and O(2)/Ar plasma. High efficiency, fine controllability and good compatibility with current plasma surface cleaning techniques may make this method an important step towards the future commercialization of photovoltaic technologies employing spiro-OMeTAD hole transport material.